2019
DOI: 10.1080/20008198.2019.1679065
|View full text |Cite
|
Sign up to set email alerts
|

Trauma during humanitarian work: the effects on intimacy, wellbeing and PTSD-symptoms

Abstract: Background: Organizations assisting refugees are over burdened with the Syrian humanitarian catastrophe and encounter diverse difficulties facing the consequences of this massive displacement. Aid-workers experience the horrors of war through their efforts to alleviate suffering of Syrian refugees. Objective: This study of Syrian refugee aid-workers in Jordan examined work-stressors identified as secondary traumatic stress (STS), number of refugees assisted, worker feelings towards the organization, and their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 52 publications
2
27
0
Order By: Relevance
“…Though Jordan has generously hosted the Syrian refugees and humanitarian organizations had the best intentions to provide their needs, many refugees are still facing challenges ( Rizkalla and Segal, 2019a , 2020 ), especially economically ( Miller and Rasmussen, 2017 ; Walton, 2018 ). For many women who enormously struggle on a daily basis in Jordan, the one thing that they aspired for and gave them hope to survive, regardless of how tangible the aspiration was—they all longed to return home—to Syria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though Jordan has generously hosted the Syrian refugees and humanitarian organizations had the best intentions to provide their needs, many refugees are still facing challenges ( Rizkalla and Segal, 2019a , 2020 ), especially economically ( Miller and Rasmussen, 2017 ; Walton, 2018 ). For many women who enormously struggle on a daily basis in Jordan, the one thing that they aspired for and gave them hope to survive, regardless of how tangible the aspiration was—they all longed to return home—to Syria.…”
Section: Discussionmentioning
confidence: 99%
“…Millions were forcibly displaced, lost their properties and social support systems ( Jabbar and Zaza, 2014 ; Balcilar and Nugent, 2019 ). They witnessed and experienced traumatic events including combat situations, killings, hunger, physical and sexual assault, as well as torture, and forced separation from family, friends, and communities ( Panter-Brick et al, 2018 ; Rizkalla and Segal, 2018 , 2019a ). In search of safety, they fled to the neighboring countries and beyond.…”
Section: Introductionmentioning
confidence: 99%
“…Well-being can be defined as a combination of both subjective and psychological well-being; for instance, happiness, life satisfaction, positive relations with others, and goal-directed behavior (12). Research has reliably shown an increase in negative symptoms such as stress and anxiety for people with low well-being (13)(14)(15)(16)(17). Recent studies investigating the impact of the COVID-19 pandemic on mental well-being have corroborated that adults who reported higher well-being as the lockdown continued exhibited reduced psychiatric symptoms (18) and improved overall work performance (19).…”
Section: Introductionmentioning
confidence: 99%
“…Humanitarian personnel are particularly susceptible to secondary traumatic stress, compassion fatigue or vicarious traumatization (Figley, 1995(Figley, , 1998McCann & Pearlman, 1990;Pearlman & Saakvitne, 1995). Such indirect exposure to a traumatic event can result in changes to memory systems, and prior views of self and the world (Figley, 1995;McCann and Pearlman 1990;Pearlman and Saakvitne 1995).…”
Section: Introductionmentioning
confidence: 99%